Studies on high-frequency noise characteristics in deep submicron NMOSFETs - Zeng, Rong (2010)
RF noise characterstics of deep sub-micrometer MOSFETs are nvestigated in this work. The direct matrix method to extract the channel thermal noise and induced gate noise is analyzed. In deep sub micron NMOSFETs, the contributions from some extrinsic elements are small and can be neglected. The procedure can therefore be simplified to a one-step matrix calculation. The obtained noise currents from the new method are in good agreement with those calculated from classical methods. The impact of Flower-Nordheim (FN) stress and oxide breakdown on high frequency noise characteristics in 0.18um NMOSFET has been studied. Noise characteristics of the devices at different leakage levels and breakdown hardness are compared. The results show a strong dependence of degradation of noise parameters on the gate leakage. The degradation mechanisms are analyzed by extraction of the channel and gate noise using a noise equivalent circuit model. It has been found that gate shot noise, which is commonly ignored in NMOSFETs, plays a dominant role in determining the high frequency noise in the post-oxide breakdown NMOSFETs. The relation between the location of gate oxide breakdown in deep submicron MOSFETs and noise characteristics has been studied. RF Noise in the frequency range of 2 to 18 GHz of the devices with oxide breakdown at different locations are characterized and compared. The results show that degradation of noise parameters subject to gate oxide breakdown is not only related to breakdown hardness but also the oxide breakdown path. For similar breakdown hardness, formation of the breakdown path closer to source side may result in a larger degradation of device RF noise performance. RF noise in 0.18um NMOSFETs concerning the contribution of carrier heating and hot carrier effect is characterized and analyzed in detail. A novel approach is used to modulate the channel carrier heating and number of hot carriers using body bias. We confirm qualitatively a negligible role of hot carrier effect on the channel noise in deep-sub micrometer MOSFETs. For a device under reverse body bias (Vb), even though the increase in hot carrier population is clearly characterized by DC measurements, the device high-frequency noise is found to be irrelevant to the increase in the channel hot carriers. Experimental results show that the high-frequency noise is slightly reduced with the increase in body bias, and can be qualitatively explained by secondary effects such as the suppression of nonequilibrium channel noise and substrate induced noise. The reduction of minimum noise figure with the increase in body bias may provide a possible methodology to finely adjust the device high-frequency noise performance for circuit design.